Potential Development Of Gold Mines As A Source Of Community Income In Muarasipongi District, Mandailing Natal Regency Using The Triple Helix Model - Hanifah, Wardah; Sugianto, Sugianto (UNIVERSITAS PAKUAN, 2017)
This study aims to analyze the potential of mines in Muarasipongi sub-district. The first village where gold mining was opened by locals was Bandar panjang tuo village which is close to the mountains of this village including remote villages, new villages of aek botung, ranjo batu etc. The source of income in various villages was initially in the agricultural sector, namely rubber, coffee and chocolate plantations, but over time and prices of agricultural products decreased, especially rubber, many farmers were willing Agriculture is declining, especially rubber, many farmers have become miners, where the results of mining can be obtained per day instead of per week or month. This gold mine does not have an official permit from the government or can be called illegal, lack of attention from the government and counseling and public knowledge about licensing and also the mine is mostly opened on land owned by the villagers not government land